Hubungan Self Efficacy dan Self Esteem Dengan Perilaku Berisiko Remaja - Andayani, Sri Astutik; Maghfiroh, Nahdia Fiki; Anggraini, Novita Riska (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
This study aims to analyze the relationship between self-efficacy and self-esteem, with juvenile delinquency. The population of this study were students of Nurul Jadid University with a sample of 120 aged between 19-21 years. The sampling technique used is simple random sampling. The data collection tool in this study was a Likert scale. This study uses statistical analysis of the Spearman rho correlation. The results show that there is a significant relationship between self-efficacy, self-esteem, and juvenile delinquency. There is a correlation between self-efficacy and juvenile delinquency (p=0.000), there is a correlation between self-esteem and juvenile delinquency (p=0.000). The higher the self-efficacy and self-esteem, the juvenile delinquency tends to be low or not at risk.